(untitled) (Philological Studies, 2019)
The article analyses Old Romance geographical names borrowed and integrated into early South Slavic. The late Proto-Slavic sound changes which were still operative during the first Romance-Slavic language contacts after the settling of the Slavs in the Balkan Peninsula, the Pannonian Basin and eastern Alps in the second half of the 6th century and the beginning of the 7th century will be categorized and chronologically ordered with the help of Romance-Slavic substitutional phonology.